The frontal and posterior cortical areas involved in the non-spatial visual allocation of attention in the human brain: a functional neuroimaging study - Drudik, Kristina; Zlatkina, Veronika; Barbeau, Elise B.; Petrides, Michael (Frontiers in Neuroscience, 2025)
Previous functional neuroimaging studies had demonstrated the involvement of cytoarchitectonic area 8Av of the prefrontal cortex in the cognitive allocation of attention to spatial stimuli. The present functional magnetic resonance imaging (fMRI) study examined brain activity related to the allocation of attention to non-spatial visual stimuli, i.e., stimuli that are defined by their perceptual features and are independent of their location. The study established (a) the involvement of area 8Av in the allocation of attention to non-spatial stimuli in the environment and (b) the areas co-activated with area 8Av across the entire cortex so that the complete functional cortical network could be defined. Finally, based on individual subject analysis, the functional activity in area 8Av was related to specific sulci in the caudal middle frontal gyrus. The novel information provided by the current fMRI study significantly advances our understanding of the role of area 8Av in the selective allocation of attention to stimuli in the environment.